5 Minute Teddy Bear Tales - Nicola Baxter (Italy Smithmark Publishers, 1998)
This book is full of 5 minute stories to read with your child before bed.
"A treasury of sleeptime stories"--Subtitle on cover.
Keywords: Anthology - Fiction -- Anthology - Fiction